Determination Of Total Flavonoid Content In 70% Ethanol Extract Of Temulawak Rhizome (Curcuma Xanthorrhiza Roxb.) From Takalar (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: Traditional medicine derived from Indonesia's natural resources has been extensively utilized by local communities for centuries. Curcuma xanthorrhiza Roxb. (temulawak) is a prominent medicinal plant in Indonesian traditional medicine, but its phytochemical content, particularly flavonoids, can be significantly influenced by geographical origin and environmental factors. Objective: This study aimed to determine the total flavonoid content in a 70% ethanol extract of temulawak rhizomes sourced from the lowlands of Takalar Regency, South Sulawesi, Indonesia. Methods: This experimental laboratory study employed maceration extraction method using 70% ethanol as solvent. Qualitative analysis was performed using the Wilstater test, while quantitative analysis was conducted using the aluminum chloride (AlCl₃) colorimetric method with UV-Vis spectrophotometry, using quercetin as the standard reference compound. Results: The extraction process yielded 12.66% extract recovery. Qualitative testing confirmed the presence of flavonoids with the formation of brownish-red coloration. Quantitative analysis revealed an exceptionally high total flavonoid content of 405.902±5.57 mg Quercetin Equivalents per gram of extract (mgQE/g). The quercetin calibration curve demonstrated excellent linearity with a regression equation of y=0.0108x+0.065 and a coefficient of determination (R²) of 0.9995. Conclusion: This study concludes that temulawak rhizome from the specific lowland region of Takalar Regency represents an exceptionally rich source of flavonoids, providing strong scientific rationale for its traditional medicinal applications and highlighting the critical importance of geographical origin in sourcing high-quality phytopharmaceutical raw materials.